2021
DOI: 10.1002/clc.23655
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coronary artery disease and percutaneous coronary intervention on mid‐term outcomes in patients with aortic valve stenosis treated with transcatheter aortic valve implantation

Abstract: Background A high frequency of coronary artery disease (CAD) is reported in patients with severe aortic valve stenosis (AS) who undergo transcatheter aortic valve implantation (TAVI). However, the optimal management of CAD in these patients remains unknown. Hypothesis We hypothesis that AS patients with TAVI complicated by CAD have poor prognosis. His study evaluates the prognoses of patients with CAD and severe AS after TAVI. Methods We divided 186 patients with severe AS undergoing TAVI into three groups: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Only three studies reported a clear percentage of the success rate, which ranged from 92.3% (Ferreira-Neto et al, 2019) to 100% (Perrin et al, 2022). One study reported that 15.6% of cases demonstrated a success rate without any complications (Kaihara et al, 2021). The majority of the included studies reported that TAVI/ TAVR combined with the PCI technique is a safe and efficacious procedure for managing patients with AS.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Only three studies reported a clear percentage of the success rate, which ranged from 92.3% (Ferreira-Neto et al, 2019) to 100% (Perrin et al, 2022). One study reported that 15.6% of cases demonstrated a success rate without any complications (Kaihara et al, 2021). The majority of the included studies reported that TAVI/ TAVR combined with the PCI technique is a safe and efficacious procedure for managing patients with AS.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Table 1 includes the sociodemographic characteristics. All of the included studies comprised patients with underlying CAD except four studies (Denimal et al, 2021;Kaihara et al, 2021;Matta et al, 2021;Tran et al, 2022). A total of 6252 patients were included.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Nevertheless, indication for treatment of significant CAD in TAVI setting still remains a matter of debate, due to the marked inconsistency of the available evidence, which are mainly based on nonrandomized data. 2,[5][6][7][8][9][10][11][12] In fact, whether performing PCI and achieving complete revascularization in patients undergoing TAVI would offer a clinical benefit in patients with significant CAD remains unclear. 13 The randomized, noninferiority ACTIVATION trial (Percutaneous Coronary Intervention Prior to Transcatheter Aortic Valve Implantation) showed that rates of death and rehospitalization at 1 year were similar between PCI and no PCI prior to TAVI.…”
mentioning
confidence: 99%